Differences in characteristics and interactions with close contacts among PWID in the San Diego Border Region before and during the COVID-19 pandemic - Lara K Marquez; Natasha K Martin; Steffanie A Strathdee; Britt Skaathun (Journal of Migration and Health)
Background: Travel restrictions implemented to mitigate the spread of SARS-CoV-2 decreased mobility and reduced physical contact during 2020–2021 for many in the general population. This analysis explored changes to network contacts among people who inject drugs (PWID) in the San Diego Border Region (SDBR) by cross-border mobility before and during the COVID-19 era. Methods: Baseline data collected between October 2020–2021, from a cohort study of PWID in the SDBR were used to retrospectively describe differences in baseline characteristics across cross-border PWID groups (cross-border PWID [CB-PWID]: n = 206; San Diego PWID [SD-PWID]: n = 203; Tijuana PWID [TJ-PWID]: n = 202). Chi-square and Fisher's exact tests evaluated sociodemographic, injecting risk behaviors, harm reduction service history, incarceration history, non-fatal overdose, HCV, HIV. Median differences in sex, drug/alcohol, and close partners before and during the pandemic among all PWID and by cross-border PWID status were evaluated using Kruskal-Wallis tests. Pairwise associations across cross-border PWID groups were assessed using the Dwass, Steel, Critchlow-Fligner multiple comparison test. Results: Among 611 PWID, the number of sex, drug/alcohol-related partners and close contacts before and during the pandemic remained relatively stable (psex=0.71;pdrug/alcohol=0.15;pclose=0.09). PWID in San Diego experienced the greatest difference in drug/alcohol-related partners (median[IQR]:-1[-6,0]), while cross-border PWID reported the smallest change in close contacts versus pre-pandemic (median[IQR]:0[0,1]). PWID in Tijuana had the greatest proportion (87%) of close contacts who injected drugs of all three groups. Conclusions: Compared to pre-pandemic, the median number of sex partners, drug/alcohol-related partners, and close contacts remained stable among PWID in the SDBR. Future research should explore how these network contacts evolve over time.